Tipe dan Gaya Kepemimpinan dalam Manajemen Pendidikan Islam - Takwim, Takwim; Bustamam, Risman (PT PUSTAKA CENDEKIA GROUP, 2023)
This study presents a literature review on the types and leadership styles in the context of Islamic education management. It aims to analyze relevant types of leadership and examine the effective leadership styles contributing to the success of Islamic education management. Through a comprehensive literature review, various types of leadership, including transformational, instructional, participative, and values-based leadership, are identified in the context of Islamic education management. Effective leadership styles such as consultative, collaborative, and visionary approaches are also analyzed based on relevant literature. The study emphasizes the importance of understanding and implementing leadership types and styles that align with Islamic values in Islamic education management. Strong leadership based on Islamic values has a positive impact on organizational culture, teaching quality, and staff development in Islamic educational institutions. The findings of this literature review provide valuable insights into the relevant types and leadership styles in Islamic education management. The study offers guidance for Islamic education leaders in leading and managing educational institutions. Furthermore, it contributes to a better understanding of the role of leadership in Islamic education and serves as a foundation for further research in this field.